2020
DOI: 10.1002/mgg3.1282
|View full text |Cite
|
Sign up to set email alerts
|

Acromicric dysplasia with stiff skin syndrome‐like severe cutaneous presentation in an 8‐year‐old boy with a missense FBN1 mutation: Case report and literature review

Abstract: BackgroundAcromicric dysplasia is a rare heritable short‐stature syndrome with joint stiffness and varying degrees of cutaneous hardness. Stiff skin syndrome is a rare connective tissue disorder characterized by diffusely thick and hard skin from the time of birth. Heterozygous point mutations in the FBN1 have been proposed as the predominant cause of both diseases.MethodsBy performing skin biopsy, X‐ray imaging, electrocardiography, as well as whole‐genome sequencing and Sanger sequencing, we diagnosed an 8‐y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The result revealed a missense c.3525A to G (p.Ile1175Met) variant in the exon 29 of FBN1 gene, which was unreported previously. The occurrence of pathogenic variants in the FBN1 gene can cause Geleophysic dysplasia type 2, 9) Acromicric dysplasia, 10) Weill-Marchesani syndrome type 2, 11) Marfan syndrome, 12,13) and stiff skin syndrome 10) are all inherited in an autosomal dominant manner. Bioinformatics analysis suggested that the variant can cause amino acid replacement and affect the structure and function of fibrillin-1.…”
Section: Discussionmentioning
confidence: 99%
“…The result revealed a missense c.3525A to G (p.Ile1175Met) variant in the exon 29 of FBN1 gene, which was unreported previously. The occurrence of pathogenic variants in the FBN1 gene can cause Geleophysic dysplasia type 2, 9) Acromicric dysplasia, 10) Weill-Marchesani syndrome type 2, 11) Marfan syndrome, 12,13) and stiff skin syndrome 10) are all inherited in an autosomal dominant manner. Bioinformatics analysis suggested that the variant can cause amino acid replacement and affect the structure and function of fibrillin-1.…”
Section: Discussionmentioning
confidence: 99%
“…The rhGH treatment received by two of our patients confirmed its limited efficacy (de Bruin et al, 2016; Jin et al, 2017). Although the subtypes of acromelic dysplasia have been divided according to major disease‐specific symptoms such as ectopia lentis in WMS and cardiac valvular stenosis in GD, recent studies have shown that FBN1 mutations can lead to a mixed phenotype of both GD and AD (Cheng et al, 2017; Moey, Flaherty, & Zankl, 2019; Wang et al, 2020). Moreover, as these cases are identified during childhood, it could be too early to observe the full clinical spectrum (Marzin, Cormier‐Daire, & Dysplasia, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Attempted pharmacotherapy should be carefully performed, while LST and MPA may help to delay the progression of widespread SSS. Entities which ought not to be diagnosed as genuine SSS Parana hard-skin syndrome with visceral involvement, 28 FBN1 mutations presenting as Acromicric dysplasia combined with SSS-like features, 29 Marfan syndrome with SSS-like features, 14 and so forth Abbreviation: SSS, stiff skin syndrome.…”
Section: Rehabilitation Exercise Remains the Cornerstone Treatment Of...mentioning
confidence: 99%